Poverty Penalty: A Market-Based Review (Global Journal of Human-Social Science, 2022)
Summery-The poverty penalty is the price that the poor pay more than the rich to obtain the same or similar goods. To be consistent with the way this concept is presented in the author who originally deals with it (Caplovitz) and in the author who originally calls it (Prahalad), the understanding of means "similar" concerns a quality standard imposed on the consumer as a condition of its functioning in society. The sociological relationships that determine this pattern, shape, through the institutions participating in the market, the economic ecosystem (so called by Prahalad). In view of this, the fight against that penalty is of questionable success in the absence of interventions to treat the sociological bases from which it is generated, which, in turn, implies that the measurements that lend themselves to identifying the penalty of poverty, need to include the effects of those sociological determinants, in the absence of which, they are useful as an exploratory data analysis, which only suggests the existence of the poverty penalty but does not actually verify it. In order to be consistent with the pioneering authors in the treatment of the penalization of poverty, the concept needs to be understood in the context of markets, or market-based. In this sense, related concepts are presented in the literature, such as "catastrophic expenses", "out-ofpocket" expenses, "uncompensated expenses", "consumer detriment" and "double jeopardy". Taken together as market-based, these concepts point to two different ways of interpreting the penalization of poverty.